Virulence and antibiotic resistance regulation in pathogens - He, Chuan (Henry Stewart Talks, 2011)
Virulence regulation, oxidative stress from immune response can dramatically affect the virulence in certain human pathogens-antibiotic resistance-oxidative stress induced by antibiotic treatment can affect resistance-Staphyloccocus aureus-Pseudomonas aeruginosa